Mixta mediterraneensis as a novel and abundant gut symbiont of the allergen-producing domestic mite Blomia tropicalis - Erban, Tomas; Sopko, Bruno; Klimov, Pavel B; Hubert, Jan (Experimental & applied acarology, 2024)
Blomia tropicalis is an allergen-producing mite in the human environment in tropical regions. The microbiome of B. tropicalis was described using the barcode sequencing region of V4 16S rDNA and genome assemblage. Mixta mediterraneensis, previously isolated from human skin swabs, was identified as a B. tropicalis gut symbiont based on genome assembly. The microbiome contains two bacteria, Staphylococcus and M. mediterraneensis. The number of M. mediterraneensis 16S DNA copies was 106 per mite and 109 per feces in the rearing chamber based on qPCR quantification. The profile of this bacterium reached 50% of reads in the mite gut and feces. Genomic analyses revealed that the bacterium has several metabolic pathways that suggest metabolic cooperation with the mite host in vitamin and amino acid synthesis, nitrogen recycling, and antimicrobial defense. Lysozyme is present in the symbiotic bacterium but absent in the mite. The B. tropicalis microbiome contained Staphylococcus, which accelerates mite population growth. Mites can digest Staphylococcus by using specific enzymes with hydrolytic functions against bacterial cell walls (chitinases and cathepsin D), leading to endocytosis of bacteria and their degradation in lysosomes and phagosomes. Gene expression analysis of B. tropicalis indicated that phagocytosis was mediated by the PI3-kinase/Akt pathway interacting with the invasins produced by M. mediterraneensis. Moreover, the symbiont had metabolic pathways that allowed it to recycle the mite metabolic waste product guanine, known as a mite attractant. The mite host symbiont enhances mite aggregation in the feces, and the fecal-oral transmission route is excepted.
Keywords: alergeny; Mite; Enzyme; Symbionts; lidé; roztoči; Animals; Allergen; zvířata; Allergens; Humans; Mites; Digestion